Species diversity, relative abundance and microhabitat utilization of frogs at Bako National Park, Sarawak - Alvin, ak. Gamar. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The study was conducted at Bako National Park in two sampling periods to detennine the species richness and species evenness of the frogs. A total of 108 individuals of frogs, representing 15 species from five families were recorded from the study site. Forest and stream transect were used for the sampling methods. The frogs captured from a wide range of microhabitats and substrates, with some species specialized to live near the water and some distant from any body of water. Rana baramica from family Ran~dae is the most dominant species with relative abundance of l7.6%, represent 19 individuals of collection. This followed by Polypedates leucomystax from the family Rhacophoridae (16.7%), represent 18 individuals. There are few new species to Bako National Park captured and this will increase the total number of frog species in the pecies checklist.